Monte Carlo simulation of a prototypical patient dosimetry system for fluoroscopic procedures - Goertz, Lukas (Physics in medicine and biology, 2015)
The purpose of this study is to investigate feasibility of a novel real-time dosimetry method for fluoroscopically guided interventions utilizing thin-film detector arrays in several potential locations with respect to the patient and x-ray equipment. We employed Monte Carlo (MC) simulation to establish the fluoroscopic beam model to determine dosimetric quantities directly from measured doses in thin-film detector arrays at three positions: A—attached to the x-ray source, B—on the couch under the patient and C—attached to the fluoroscopic imager. Next, we developed a calibration method to determine skin dose at the entry of the beam (${D_{\text{entr}}}$ ) as well as the dose distribution along each ray of the beam in a water-equivalent patient model. We utilized the concept of water-equivalent thickness to determine the dose inside the patient based on doses measured outside of the patient by the thin-film detector array layers: (a) A, (b) B, or (c) B and C. In the process of calibration we determined a correction factor that characterizes the material-specific response of the detector, backscatter factor and attenuation factor for slab water phantoms of various thicknesses. Application of this method to an anthropomorphic phantom showed accuracy of about 1% for ${D_{\text{entr}}}$ and up to about 10% for integral dose along the beam path when compared to a direct simulation of dose by MC.
Gesehen am 11.12.2018